Pengaruh Gaya Belajar Terhadap Prestasi Belajar Peserta Didik pada Mata Pelajaran Sejarah Kebudayaan Islam - Mega Dwi Susanti (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2020)
The purpose of this research is to obtain an overview of learning styles and students ' learning achievement in the subjects of the history of Islamic culture at Madrasah Ibtidaiyah Podorejo in Tulungagung. The research method used is a survey method. The survey was conducted on students of class III E.G. Podorejo of Tulungagung City with a total of 71 people. Sample determination of simple random sampling method. Retrieval of research data is taken using tests and documentation. The results showed that the students of the III grade Podorejo the Tulungagung city as many as 25 students (35.2%) Has a visual learning style, 25 learners (35.2%) has auditory learning style, and 21 learners (29.6%) Have a kinaesthetic learning style. From this data indicates that the class III Podorejo MIS in Tulungagung City tends to have a visual and auditory learning style.